ANALYZING THE MEANING OF LANGUAGE USE IN POLITENESS STRATEGIES IN THE DANISH GIRL MOVIE - Rahma Melati; Sabaruddin (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2022)
Politeness strategies are used to craft messages that save the listener's positive and negative face when face-threatening behavior is inevitable or desired. Brown and Levinson mainly outline his four types of politeness strategies. Do not use baldness, negative politeness, positive politeness, off the record (indirect), and simply face-threatening behavior. Positive politeness strategies try to minimize threats to the listener's positive face and make the listener feel good. Negative politeness strategies are based on avoidance and assume that the speaker is imposing something on the listener. Off-the-record strategies use indirect speech to deprive the speaker of the possibility of imposing themselves on the listener. Discourse analysis is conducted to analyze the